2014
DOI: 10.1371/journal.pone.0109306
|View full text |Cite
|
Sign up to set email alerts
|

Both Transmembrane Domains of BK β1 Subunits Are Essential to Confer the Normal Phenotype of β1-Containing BK Channels

Abstract: Voltage/Ca2+ i-gated, large conductance K+ (BK) channels result from tetrameric association of α (slo1) subunits. In most tissues, BK protein complexes include regulatory β subunits that contain two transmembrane domains (TM1, TM2), an extracellular loop, and two short intracellular termini. Four BK β types have been identified, each presenting a rather selective tissue-specific expression profile. Thus, BK β modifies current phenotype to suit physiology in a tissue-specific manner. The smooth muscle-abundant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(41 citation statements)
references
References 35 publications
(76 reference statements)
8
33
0
Order By: Relevance
“…Their likely interposed location between VSDs of adjacent BKα subunits suggests a role in modulating voltage-sensor activation. The two TM segments in β1 subunit were functionally replaceable by those from the β2 subunit (Orio et al, 2006) but not from the β4 subunit even replaced individually (Kuntamallappanavar, Toro, & Dopico, 2014). The latter showed that both TM segments are required to maintain the characteristic modulatory function of the β1 subunit (Kuntamallappanavar et al, 2014).…”
Section: Modulation Of the Bk Channel's Biophysical Properties By mentioning
confidence: 99%
“…Their likely interposed location between VSDs of adjacent BKα subunits suggests a role in modulating voltage-sensor activation. The two TM segments in β1 subunit were functionally replaceable by those from the β2 subunit (Orio et al, 2006) but not from the β4 subunit even replaced individually (Kuntamallappanavar, Toro, & Dopico, 2014). The latter showed that both TM segments are required to maintain the characteristic modulatory function of the β1 subunit (Kuntamallappanavar et al, 2014).…”
Section: Modulation Of the Bk Channel's Biophysical Properties By mentioning
confidence: 99%
“…Furthermore, the parallel leftward shift in the NP o /NP o max -V curve seen at physiological Ca 2+ i is consistent with an increased presence of functional BK β1 subunits [5,11,27,50,51,67,70]. Interestingly, the actual BK V half values in myocytes from BA and CA are similar to those found using heterologous expression systems in which overexpression of β1 subunits is considered to saturate their slo1 partners, including slo1 cloned from rat cerebral artery myocytes ([5,11,27,50,51,70]; e.g., at physiological 3 μM Ca 2+ i , V half values for BA, CA, and slo1+β1 overexpressed in oocytes are 23.5±5.9, 25.15±3.4 and 24.7 ± 13.0 [27]), respectively. Collectively, our electrophysiological data strongly suggest that the increased activity of myocyte BK channels in CA and BA is primarily due to an increased functional presence of BK β1 in these arteries.…”
Section: Resultsmentioning
confidence: 59%
“…On the other hand, it is widely accepted that within physiological levels of Ca 2+ i and voltage, over-expression of β1 subunits with slo1 in heterologous systems (HEK293 cells, X. laevis oocytes) leads to increased BK steady-state activity [5,11,27,50,51]. The stoichiometry of slo1 and β1 subunits in native channels across different vascular and nonvascular tissues remains largely unknown.…”
Section: Resultsmentioning
confidence: 99%
“…The proximity between the TMs of β1 and the VSD of BK channels makes it tempting to suggest that the TMs of the β1-subunit are involved in the modulation of the voltage-sensor equilibrium between resting and active configurations. This hypothesis is supported by the results of Kuntamallappanavar et al (55), who, by making chimeras between β1 and β4, proposed that both transmembrane segments of β1 are needed to confer the phenotype of α/β1 BK channels. However, the high degree of homology among β-subunit TMs and the differences in the modulation exerted by the different β-subunits (39) cast doubt on the thought that TM segments of β-subunits are the only molecular determinants involved in VSD modulation.…”
Section: Discussionmentioning
confidence: 68%